Plasma osteopontin levels in patients with Behcet's disease and psoriasis - Erturkler, Enis; Cicek, Demet; Kaman, Dilara; Ozdogan, Serhat; Dertlioglu, Selma Bakar (John Libbey Eurotext Ltd, 2011)
Background: Behcet's disease (BD) is a chronic and recurrent systemic vasculitis marked by macrophage chemotaxis. Objective: The present study aimed to examine the relationship between the osteopontin molecule and BD. Patients and Methods: The study registered 60 patients with BD, as well as 50 healthy individuals and 63 patients with psoriasis as the control group. Patients with BD in our study were divided into 2 groups, with regard to mucocutaneous involvement, as active and inactive patients. In addition, patients with BD were also divided into 3 groups with regard to vascular involvement: active, inactive, and no vascular involvement. Results: Plasma osteopontin (OPN) levels in active patients with BD, inactive patients with BD and patients with psoriasis were found statistically significantly elevated, in comparison to those in the healthy control group (p < 0.001, p = 0.008, p < 0.001, respectively). When active and inactive patients with BD were compared to the healthy control group with regard to vascular involvement, mean plasma OPN levels were found to be statistically significantly higher (p = 0.01, p < 0.001, respectively). Conclusions: We found that plasma levels of OPN were higher in patients with Behcet's and psoriasis.
Keywords: Behcet's disease; psoriasis; osteopontin